1987
DOI: 10.1002/bip.360260203
|View full text |Cite
|
Sign up to set email alerts
|

Number of binding sites of DNA and polynucleotides with tris(2,2′‐bipyridyl)ruthenium(II) cations

Abstract: SynopsisThe binding of tris(2,2'-bipyridyl)ruthenium(II) cations [Ru(bpy)$+ ] with single-and doublestranded (ss and ds) DNA, and the polynucleotides poly(A), poly(C), poly(G), poly(I), poly(1) .poly(C), and poly(U), was studied in aqueous solution. Steady-state electrical conductivity measurements with the polynucleotides, ssDNA, and dsDNA reveal that approximately three nucleotides offer one binding site. This may be compared with the ratio [nucleotide]/[Mg*+] of 2.4 : 1 for dsDNA. After laser excitation (35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…In previous work we have shown that under certain conditions Ru(bpy):+ is attached to nucleic acids (Stradowski et al, 1987). Under these conditions the luminescence exhibits a bi-exponential decay pattern after ns-laser excitation.…”
Section: Introductionmentioning
confidence: 91%
“…In previous work we have shown that under certain conditions Ru(bpy):+ is attached to nucleic acids (Stradowski et al, 1987). Under these conditions the luminescence exhibits a bi-exponential decay pattern after ns-laser excitation.…”
Section: Introductionmentioning
confidence: 91%
“…The remaining benzoylhydrazone moiety is disposed along the sugar-phosphate backbone, which through polar interaction with the charged sugar-phosphates restricts the free insertion (intercalation) of the phen groups. The bpy-metal counterparts, due to non-planarity of the bpy molecule [27][28][29], binds DNA very weakly though intercalative mode due to the predominant polar interaction of the benzoylhydrazone with the negatively charged deoxyribose-phosphate backbone.…”
Section: Electrochemical Behaviormentioning
confidence: 99%
“…These isotherms show that much more probe is bound to outer ds-DNA layers than outer ss-DNA layers. The Co(bpy) 3 3 binding site size for ds-DNA and ss-DNA is 3 base pairs [30,54,55]. Available DNA binding sites in the outer layer were estimated under saturation conditions using the difference in the integrated coulometric charge (Q c ) between (PDDA/DNA) 2 and PDDA/DNA/PDDA films.…”
Section: To Dna Filmsmentioning
confidence: 99%